Impact of Social Media Marketing on Consumers in Philippines - Marie, Alyssa (International Journal of Fashion and Design, 2024)
Purpose: The aim of the study was to analyze the impact of social media marketing on consumers in Philippines. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The impact of social media marketing on consumers in the Philippines reveals that platforms like Facebook, Instagram, and Twitter significantly influence purchasing behavior, especially among younger audiences. Studies show that Filipino consumers are highly engaged with brands on social media, where personalized content, influencer marketing, and customer interaction drive brand loyalty and product awareness. Social media also facilitates quicker decision-making, as consumers rely on peer reviews and recommendations before making purchases. However, challenges include issues with data privacy and the oversaturation of promotional content, which can lead to consumer fatigue. Unique Contribution to Theory, Practice and Policy: Theory of planned behavior (TPB), uses and gratifications theory (UGT) & social influence theory may be used to anchor future studies on the impact of social media marketing on consumers in Philippines. Companies should invest in analytics tools to understand consumer preferences, enabling them to create more personalized and engaging content. Policymakers should develop regulations that ensure transparency in social media advertising and influencer endorsements, particularly in areas like disclosure of paid partnerships.